210k views
3 votes
Any 10th grader solve it
for 50 points​

Any 10th grader solve it for 50 points​-example-1
User Rplnt
by
6.0k points

1 Answer

6 votes

Answer:


(a)/(p)* (q-r)+(b)/(q)* (r-p)+(c)/(r)* (p-q)\\eq 0 is proved for the sum of pth, qth and rth terms of an arithmetic progression are a, b,and c respectively.

Explanation:

Given that the sum of pth, qth and rth terms of an arithmetic progression are a, b and c respectively.

First term of given arithmetic progression is A

and common difference is D

ie.,
a_(1)=A and common difference=D

The nth term can be written as


a_(n)=A+(n-1)D

pth term of given arithmetic progression is a


a_(p)=A+(p-1)D=a

qth term of given arithmetic progression is b


a_(q)=A+(q-1)D=b and

rth term of given arithmetic progression is c


a_(r)=A+(r-1)D=c

We have to prove that


(a)/(p)* (q-r)+(b)/(q)* (r-p)+(c)/(r)* (p-q)=0

Now to prove LHS=RHS

Now take LHS


(a)/(p)* (q-r)+(b)/(q)* (r-p)+(c)/(r)* (p-q)


=(A+(p-1)D)/(p)* (q-r)+(A+(q-1)D)/(q)* (r-p)+(A+(r-1)D)/(r)* (p-q)


=(A+pD-D)/(p)* (q-r)+(A+qD-D)/(q)* (r-p)+(A+rD-D)/(r)* (p-q)


=(Aq+pqD-Dq-Ar-prD+rD)/(p)+(Ar+rqD-Dr-Ap-pqD+pD)/(q)+(Ap+prD-Dp-Aq-qrD+qD)/(r)


=([Aq+pqD-Dq-Ar-prD+rD]* qr+[Ar+rqD-Dr-Ap-pqD+pD]* pr+[Ap+prD-Dp-Aq-qrD+qD]* pq)/(pqr)


=(Arq^(2)+pq^(2) rD-Dq^(2) r-Aqr^(2)-pqr^(2) D+qr^(2) D+Apr^(2)+pr^(2) qD-pDr^(2) -Ap^(2)r-p^(2) rqD+p^(2) rD+Ap^(2) q+p^(2) qrD-Dp^(2) q-Aq^(2) p-q^(2) prD+q^(2)pD)/(pqr)


=(Arq^(2)-Dq^(2)r-Aqr^(2)+qr^(2)D+Apr^(2)-pDr^(2)-Ap^(2)r+p^(2)rD+Ap^(2)q-Dp^(2)q-Aq^(2)p+q^(2)pD)/(pqr)


=(Arq^(2)-Dq^(2)r-Aqr^(2)+qr^(2)D+Apr^(2) -pDr^(2)-Ap^(2)r+p^(2)rD+Ap^(2)q-Dp^(2)q-Aq^(2)p+q^(2)pD)/(pqr)


\\eq 0

ie.,
RHS\\eq 0

Therefore
LHS\\eq RHS

ie.,
(a)/(p)* (q-r)+(b)/(q)* (r-p)+(c)/(r)* (p-q)\\eq 0

Hence proved

User Revolutionary
by
6.2k points